The mitochondrial isoform of phosphoenolpyruvate carboxykinase (PEPCK-M) and glucose homeostasis: Has it been overlooked? - Stark, Romana; Kibbey, Richard G. (Biochimica et biophysica acta, 2014)
Plasma glucose levels are tightly regulated within a narrow physiologic range. Insulin-mediated glucose uptake by tissues must be balanced by the appearance of glucose from nutritional sources, glycogen stores, or gluconeogenesis. In this regard, a common pathway regulating both glucose clearance and appearance has not been described. The metabolism of glucose to produce ATP is generally considered to be the primary stimulus for insulin release from beta-cells. Similarly, gluconeogenesis from phosphoenolpyruvate (PEP) is believed to be the primarily pathway via the cytosolic isoform of phosphoenolpyruvate carboxykinase (PEPCK-C). These models cannot adequately explain the regulation of insulin secretion or gluconeogenesis. A metabolic sensing pathway involving mitochondrial GTP (mtGTP) and PEP synthesis by the mitochondrial isoform of PEPCK (PEPCK-M) is associated with glucose-stimulated insulin secretion from pancreatic beta-cells. Here we examine whether there is evidence for a similar mtGTP-dependent pathway involved in gluconeogenesis. In both islets and the liver, mtGTP is produced at the substrate level by the enzyme succinyl CoA synthetase (SCS-GTP) with a rate proportional to the TCA cycle. In the beta-cell PEPCK-M then hydrolyzes mtGTP in the production of PEP that, unlike mtGTP, can escape the mitochondria to generate a signal for insulin release. Similarly, PEPCK-M and mtGTP might also provide a significant source of PEP in gluconeogenic tissues for the production of glucose. This review will focus on the possibility that PEPCK-M, as a sensor for TCA cycle flux, is a key mechanism to regulate both insulin secretion and gluconeogenesis suggesting conservation of this biochemical mechanism in regulating multiple aspects of glucose homeostasis. Moreover, we propose that this mechanism may be important for regulating insulin secretion and gluconeogenesis compared to canonical nutrient sensing pathways. PEPCK-M, initially believed to be absent in islets, carries a substantial metabolic flux in beta-cells. This flux is intimately involved with the coupling of glucose-stimulated insulin secretion. PEPCK-M activity may have been similarly underestimated in glucose producing tissues and could potentially be an unappreciated but important source of gluconeogenesis. The generation of PEP via PEPCK-M may occur via a metabolic sensing pathway important for regulating both insulin secretion and gluconeogenesis. This article is part of a Special Issue entitled Frontiers of Mitochondrial Research. The mitochondrial isoform of phosphoenolpyruvate carboxylase (PEPCK-M) plays an important role in glucose homeostasis. As PEPCK-M is constitutively expressed and dependent upon mitochondrial GTP (mtGTP), it is well disposed to link the mitochondrial energy sensing signal “mtGTP” with insulin secretion in the pancreas (left) or glucose production (right) in the liver. Glucose that enters the β-cells of the pancreas (left) is degraded to phosphoenolpyruvate (PEP) during glycolysis and metabolized to pyruvate. Pyruvate that enters the TCA cycle by pyruvate dehydrogenase (PDH) will generate GTP via direct synthesis by SCS-GTP. Anaplerotic pyruvate entry by pyruvate carboxylase (PC) will generate oxaloacetate. PEPCK-M will then consume oxaloacetate and GTP to produce PEP. In contrast to the pancreas, the liver has two PEPCK isoforms: cytosolic (PEPCK-C) and mitochondrial (PEPCK-M) and both produce PEP when there is adequate TCA flux (right). PEP can then be used for gluconeogenesis. The mtGTP/PEPCK-M pathway is a hormone-independent gluconeogenic pathway. GDH glutamate dehydrogenase. [Display omitted] •Mitochondrial GTP (mtGTP) is produced at a rate proportional to TCA cycle flux.•PEPCK-M activity is dependent on mtGTP and thus linked to TCA cycle flux.•A mtGTP cycle between the enzymes SCS-GTP and PEPCK-M generates mitochondrial PEP.•The mtGTP cycle couples glucose metabolism to insulin secretion.•Mitochondrial PEP (mtPEP) generated by PEPCK-M may be a significant source of gluconeogenic flux.